Dipolar 1,3-Cycloaddition:Synthesis of New Pyrazolinic Compounds Derived From Eugenol (Global Journal of Science Frontier Research, 2015)
Abstract not found
Keywords: dipolar 1; 3-cycloaddition; synthesis; eugenol; pyrazolinic compounds